Fabrication of Proton-Exchange Waveguide Using Stoichiometric LiTaO3 for Guided Wave Electrooptic Modulators with Polarization-Reversed Structure. (16th November 2008) - Murata, Hiroshi; Okamura, Yasuyuki
Abstract : Optical waveguides were fabricated on z-cut stoichiometricLiTaO 3 (SLT) by using the proton-exchange method. The surface index change for the extraordinary ray on the SLT substrate resulting from the proton exchange was 0.017, which coincided well with congruentLiTaO 3 substrates. The proton exchange coefficient in the SLT was0.25 × 10 − 12   cm 2 / s . The application of the SLT waveguide to a quasi-velocity-matched travelling-wave electrooptic modulator with periodically polarization-reversed structure is also reported.